Маркетингове управління бізнес-процесами оптових торговельних підприємств - Багорка, Марія Олександрівна; Bahorka, Mariia; Юрченко, Наталія Іванівна; Yurchenko, Nataliia (Дніпропетровський науково-дослідний інститут судових експертиз України, 2021)
У статті установлено, що трансформація економіки на шляху до ринкових відносин змушує перейти й до створення нової маркетингової системи управління підприємствами оптової торгівлі, яка сьогодні виступає важелем для стимулювання розвитку вітчизняного виробництва в умовах економічної нестабільності та зміни смаків клієнтів, активізації дій конкурентів, коливання цін, попиту, ділової активності на ринку. Маркетингова концепція управління оптовою торговельною діяльністю напряму корелюється з бізнес-процесами і пов’язана з операціями з дослідження купівельного попиту, потреб постачальників і покупців, наданням оптових послуг та розробленням раціональних шляхів товароруху. Комерційні, логістичновиробничі та фінансові бізнес-операції моделюються та реалізуються за допомогою маркетингової системи управління, дають змогу об’єднувати потреби постачальників, покупців та забезпечити у своїй єдності більш раціональні способи просування товарів, аніж у разі їх відокремленої організації. It is established that the transformation of the economy on the way to market relations forces to move to the creation of a new marketing management system of wholesale trade, which today is a lever to stimulate domestic production, in conditions of economic instability and changing customer tastes, intensification of competitors, price fluctuations, demand, business activity in the market. We have identified the need to find modern approaches to managing the business processes of wholesale enterprises, which requires the formation of a holistic, scientifically sound system of organization and an effective enterprise management system. Such a system should be a marketing management concept that would be aimed at meeting the needs and demands of the market, would adequately respond to changes in the internal and external environment, would increase the profitability of sales activities. The marketing concept of management differs from production and marketing flexibility, elasticity, efficiency and sensitivity to market changes, greater adaptability to various innovations. The marketing concept of wholesale trade management is directly correlated with business processes and is related to operations to study consumer demand, the needs of suppliers and buyers, the provision of wholesale services and the development of rational ways of moving goods. Commercial, logistics, production and financial business operations are modeled and implemented through a marketing management system, combining the needs of suppliers, customers and providing in their unity more rational ways to promote goods than in the case of their separate organization. Marketing management should combine and harmonize the main business processes of the wholesale company, the result of which is: for the manufacturer the best conditions of purchase; guarantee and prospects of sales channels; placing products on the market; transportation conditions; storage conditions, motivation of employees. Management decisions are presented, the adoption of which will help to combine and harmonize the main business processes of wholesale trade enterprises and ensure their more rapid adaptation to the market environment.
Marketing management of business processes of wholesale trade enterprises
Keywords: маркетингове управління; marketing management; оптові торговельні підприємства; wholesale trade enterprises; бізнес-процеси; business processes; закупівля; procurement; збут; sales; маркетингові інструменти; marketing tools; ринок; market